Elasticities of supply for the US natural gas market - Micaela Ponce; Anne Neumann (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
In this paper we investigate natural gas producer's reactions to changes in market prices. We estimate price elasticities of aggregated supply in the most competitive market for natural gas: the United States. Using monthly time series data form 1987 to 2012 our analysis is based on an Autoregressive Distributed Lag (ARDL) Bound Cointegration approach to obtain short and long-run elasticities of natural gas supply. Results suggest that natural gas producers in a competitive market are not able to react to prices in the very short-run but respond inelastic in the long-run. These findings are not only of great value for policy makers but also for gas market modelers.
Keywords: L95; Q41; C22; C32; 330; elasticity of supply; natural gas; ARDL; ECM; competitive markets